Age‐related trends in cardiometabolic disease among adults with cerebral palsy. (27th April 2018) - Peterson, Mark D; Kamdar, Neil; Hurvitz, Edward A
Abstract : Aim: To examine the longitudinal trends of cardiometabolic diseases in a large sample of adults with cerebral palsy (CP). Method: The Optum Clinformatics Data Mart is a de‐identified nationwide claims database of beneficiaries from a single private payer. Beneficiaries were included if they had an International Classification of Diseases, Ninth Revision, Clinical Modification code for a diagnosis of CP. Adults with at least 3 years of continuous enrollment on a single plan between 2002 and 2009 were included in the final analyses ( n =2659). We examined the longitudinal trends of incident diabetes mellitus, hypercholesterolemia, hypertension, cardiac dysrhythmias, and atherosclerosis, stratified by age categories: 18 to 39 years, 40 to 59 years, and 60 years and over. Kaplan–Meier product‐limit survival curves were compared across age categories for each of the cardiometabolic outcomes, and a Cox proportional hazards regression was run to determine adjusted hazard ratios. Results: The cumulative incidence of each of the cardiometabolic diseases ranged from 6.0% for atherosclerosis to 34.4% for hypercholesterolemia at 3 years and over. Risk‐adjusted Cox proportional hazard models revealed that age was a robust predictor of survival for each outcome, with higher hazard ratio ranges in middle age (hazard ratio 1.41–2.72) and older adults (hazard ratio 2.20–5.93) compared with young adults. Interpretation: Adults with CP have high rates of cardiometabolic diseases; and disease‐free survival shortens significantly with higher ages. What this paper adds: Adults with cerebral palsy have high rates of cardiometabolic diseases. Disease‐free survival of all cardiometabolic diseases shortens significantly with higher ages. The highest rates were for hypercholesterolemia and hypertension. What this paper adds: Adults with cerebral palsy have high rates of cardiometabolic diseases. Disease‐free survival of all cardiometabolic diseases shortens significantly with higher ages. The highest rates were for hypercholesterolemia and hypertension. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by McPhee on pages 390–391 of this issue. Video Podcast: https://www.youtube.com/watch?v=kynWzi7DspY&feature=youtu.be Resumen: Tendencias relacionadas con la edad en la enfermedad cardio‐metabólica en adultos con parálisis cerebral: Objetivo: Examinar las tendencias longitudinales de las enfermedades cardio‐metabólicas en una gran muestra de adultos con parálisis cerebral (PC). Método: El Data Mart de Optum Clinformatics es una base de datos de reclamaciones nacional anónima de beneficiarios de un único proveedor de servicios de salud privado. Se incluyeron los beneficiarios si tenían un Código de Clasificación Internacional de Enfermedades, Novena Revisión, Modificación Clínica para un diagnóstico de PC. Los adultos con al menos 3 años de inscripción continua en un solo plan entre 2002 y 2009 se incluyeron en los análisis finales ( n =2659). Examinamos las tendencias longitudinales de diabetes mellitus incidente, hipercolesterolemia, hipertensión, disritmias cardíacas y aterosclerosis, estratificadas por categorías de edad: de 18 a 39 años, de 40 a 59 años y mayores de 60 años. Se compararon las curvas de supervivencia del límite de producto de Kaplan‐Meier para cada categoría de edad para cada resultado cardio‐metabólico, y se realizó una regresión de riesgos proporcionales de Cox para determinar los cocientes de riesgo ajustados. Resultados: La incidencia acumulada de cada una de las enfermedades cardio‐metabólicas varió del 6.0% para la aterosclerosis al 34.4% para la hipercolesterolemia a los 3 años y más. Los modelos de riesgo proporcional de Cox ajustados por riesgo revelaron que la edad era un predictor robusto de supervivencia para cada resultado, con rangos de razón de riesgo más altos en la mediana edad (razón de riesgo 1.41–2.72) y adultos mayores (razón de riesgo 2.20–5.93) en comparación con los adultos jóvenes. Interpretación: Los adultos con PC tienen altas tasas de enfermedades cardio‐metabólicas; y la supervivencia libre de enfermedad se acorta significativamente con las edades más altas. Resumo: Tendências relacionadas à idade em doença cardio‐metabólica entre adultos com paralisia cerebral: Objetivo: Examinar as tendências longitudinais de doenças cardio‐metabólicas em uma grande amostra de adultos com paralisia cerebral (PC). Método: O Optum Clinformatics ™ Data Mart é uma base de dados nacional não‐identificada de beneficiários de um convênio privado. Os beneficiários foram incluídos se tivessem uma Classificação internacional de doenças, nona revisão, códico de modificação clínica para diagnóstico de PC. Adultos com pelo menos 3 anos de envolvimento contínuo em um único plano entre 2002 e 2009 foram incluídos na análise final ( n =2659). Examinamos as tendências longitudinais de incidência de diabetes mellitus, hipercolesterolemia, hipertensão, disritmias cardíacas e aterosclerose, estratificadas por categorias etárias: 18 a 39 anos, 40 a 59 anos, e acima de 60 anos. Curvas de sobreviência produto‐limite de Kaplan–Meier foram comparadas entre categorias etárias para cada uma das condições cardio‐metabólicas, e uma regressão de riscos proporcionais de Cox foi realizada para determinar as taxas ajustadas de risco. Resultados: A incidência cumulativa de cada doença cardio‐metabólica variou de 6.0% para aterosclerose a 34.4% para hipercolesterolemia em 3 anos ou mais. Os modelos de risco proporcionais de Cox ajustados revelaram que a idade foi um preditor robusto da sobrevivência para cada desfecho, com maior taxa de risco na meia idade (taxa de risco 1.41–2.72) e em adultos mais velhos (taxa de risco 2.20–5.93) em comparação com jovens adultos. Interpretação: Adultos com PC tem taxas altas de doenças cardio‐metabólicas; a sobrevivência sem doenças se reduz significantemente em maiores idades.